BUTTER PRODUCTION BASED ON CASHEWS - Bartuano, Liz Marie (2017)
The cashew nut is the real fruit in the cashew. This fruit is rarely used but can be easily found in Panama. There aren´t many companies that are mass-producing these types of nuts, probably because of the lack of knowledge related to this nuts. This lack of key information has limited the potential to commercialize the fruit. The objective of this investigation is to confirm and show all of the properties it can offer; also, we hope the community can benefit from these data. Prior investigations have shown that it has a lot of antioxidants, vitamins, and a low amount of cholesterol. In this study, we did characterize the cashew nut considering its humidity, total carbohydrates, proteins, lipids, and our results showed that there was a good amount of each of these components, those allowing us to conclude it has excellent chemical and physical properties that can be perceived positively our newly developed cashew nut based butter.